Effect of vanadium on the microstructure and high-temperature properties of 24CrNiMo coatings in direct laser deposition technology - Chao Zhang; Qiang Fang; Yan Liu; Dengwen Hu; Ying Wu; Chuan Yang; Lei Wang; Hui Chen (Journal of Materials Research and Technology)
24CrNiMo low alloy steel is extensively used in the high-speed rail industry for brake discs due to its superior strength and plasticity. This study presents an effective method for extending the life of brake discs through repair and remanufacturing, addressing the challenge of insufficient performance in the high temperature. By incorporating varying ratios of V elements into 24CrNiMo low alloy powders, the high temperature performance of the brake discs was significantly enhanced, and the strengthening mechanisms and failure behavior at the high temperature of V elements were systematically analyzed. The results indicate that the addition of V elements slightly increases the phase transition temperature of the coating, refines the lath martensite, and promotes the formation of the VC. The microhardness, tensile strength, and elongation of the coatings improve significantly with increasing V content, primarily due to the combined effects of precipitation strengthening, solution strengthening, and fine-grained strengthening. However, adding excessive V results in brittle fracture and a marked reduction in the plasticity of the coatings due to the precipitation and growth of VC in the grain boundary. At 600 °C, the coatings with 0.5 % V content demonstrated the optimal balance between tensile strength and elongation, whereas excessive V content caused low ductility due to the precipitation and growth of the VC. This study highlights that the performance of the coatings can be effectively optimized by adjusting the V content in the high temperature, providing both theoretical support and practical guidance for the remanufacturing of brake discs.